Using Online Discussion in the English Language Classroom: An Opportunity to Develop Critical Thinking Skills among Thai Tertiary Students - Rajprasit, Krich (University of the Thai Chamber of Commerce Journal Humanities and Social Sciences, 2019)
The citizens of a global community need to be equipped with 21st Century skills, including the ability to think critically, in order to survive in an ever-changing world. Global citizens therefore need to develop skills in response to the requirements of the ‘community’. Specifically, critical thinking skills need to be cultivated, as theoretically these skills are not considered inherent, and therefore need to be developed and enhanced. The teaching method of applying online discussion in English language classrooms is recommended for students who are required to use these skills. This article aims to review and discuss the role of critical thinking skills, and the possibility of developing these skills among Thai university students via English online discussion. The steps suggested below may provide ideas and guidelines for English education stakeholders, as well as their application in the language classroom.